2016
DOI: 10.1111/iwj.12695
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hallux Valgus related of quality of life in Women

Abstract: The purpose of this study is to analyse and compare the impact of hallux valgus (HV) in a sample of adult women with varying degrees of HV scores obtained with regard to foot health and health in general. A total 100 female patients of mean age 43·04 ± 16·84 years who attended a podiatric clinic were asked to answer a questionnaire. The degree of deformity, HV, was determined on both feet of the patients using the Manchester Scale tool and the scores from the Foot Health Status Questionnaire were compared. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 32 publications
0
26
0
1
Order By: Relevance
“…The exclusion criteria included immunodepression, histories of trauma and foot surgery, neurological alterations and lack of or only partial autonomy in performing daily activities. 19…”
Section: Respondentsmentioning
confidence: 99%
“…The exclusion criteria included immunodepression, histories of trauma and foot surgery, neurological alterations and lack of or only partial autonomy in performing daily activities. 19…”
Section: Respondentsmentioning
confidence: 99%
“…They found a reduction in QoL when deformity worsened. Lopez et al 26 , after evaluating 100 women with HV, confirmed a relationship between QoL and the bunion deformity. However, these authors used the Manchester scale to measure foot deformity, while our study used objective angular parameters measured on radiographs.…”
Section: Resultsmentioning
confidence: 90%
“…None of the participants had a neurologic condition affecting the lower limbs. [25][26][27] Sample size Having established a minimal difference score of at least 21 (as clinically relevant) among the groups under study in the FHSQ, and considering that the standard deviation on that scale for the people is around 29 28, 29 for a bilateral hypothesis, an alpha risk of 5% and a statistical power of 80%, and a beta error of 20%, at least 47 cases must be studied in each group (n=94).…”
Section: Design and Samplementioning
confidence: 99%